Photo and spectral fluorescence analysis of the spinal cord injury area in animal models - A. M. Udeneev; N. A. Kalyagina; V. F. Reps; V. V. Kozlova; L. A. Pigunova; D. I. Pozdnyakov; A. S. Skobeltsin; V. B. Loschenov (Biomedical Photonics)
The purpose of the work is to follow the dynamics of changes in fluorescent signals in the near-surface layers of tissue of injured areas of the back of laboratory animals, which will allow, by indirect evidence, to evaluate the information content of fluorescence diagnosis for subsequent possible diagnostic monitoring of photodynamic therapy of the spinal cord. The model animals were Wistar rats. Two types of contusions were modeled: pneumo-contusion and contusion by a falling load. Methylene blue and indocyanine green were used as photosensitizers. Fluorescence measurements were carried out by imaging and spectrometric methods. A stroboscopic fluorescence imager with an excitation wavelength of 630 nm was used to acquire fluorescence images. The LESA-01-BIOSPEC  spectrometer with a He-Ne laser excitation allowed to obtain spectra. It was shown that both methods make it possible to estimate the fluorescence value of methylene blue and indocyanine green in the tissues under study. Moreover, the photographic method also allows to obtain the spatial distribution of fluorescence. The general trend found in the data is a more intense and uniform fluorescence of the dorsal region of rats with methylene blue and a less intense, but more contrasting distribution of indocyanine green. The presented methods are non-invasive, which makes them attractive for diagnostic use. However, due to the shallow depth of signal reception, the condition of the spine can be determined only indirectly, by the condition of the near-surface layers of tissue that accumulate the photosensitizer.